Dead man's burden [videorecording (DVD)] - Moshé, Jared; Moshé, Jared; Jacobs, Barlow; Bowen, Clare, 1989-; Call, David, 1982-; Taylor, Joseph Lyle, 1964-; Riehle, Richard, 1948- (Flatiron Film Company : Cinedigm Entertainment, 2013)
A western set on the New Mexico frontier a few years after the Civil War and centered on a struggling young family and the mining company who wants to buy their land.